Instructor's manual to accompany : - Bodnar, George H. (Allyn and Bacon, 1987)
This interesting, extremely useful book stresses information, communication, and networking technology within the realm of business processes and internal control structure. Its brief yet comprehensive coverage has been updated to include all of the latest AIS topics, such as: electronic commerce, electronic security, web commerce, internet security, network security, statistical sampling and artificial intelligence, EDI, databases, and encryption.